A Robust Method for the Elaboration of SiO2-Based Colloidal Crystals as a Template for Inverse Opal Structures - Fookes, Federico Adrian (2023)
Photonic crystals (PCs) are nanomaterials with photonic properties made up of periodically modulated dielectric materials that reflect light between a wavelength range located in the photonic band gap. Colloidal PCs (C-PC) have been proposed for several applications such as optical platforms for the formation of physical, chemical, and biological sensors based on a chromatic response to an external stimulus. In this work, a robust protocol for the elaboration of photonic crystals based on SiO2 particle (SP) deposition using the vertical lifting method was studied. A wide range of lifting speeds and particle suspension concentrations were investigated by evaluating the C-PC reflectance spectrum. Thinner and higher reflectance peaks were obtained with a decrease in the lifting speed and an increase in the SP concentrations up to certain values. Seven batches of twelve C-PCs employing a SP 3% suspension and a lifting speed of 0.28 µm/s were prepared to test the reproducibility of this method. Every C-PC fabricated in this assay has a wavelength peak in a range of 10 nm and a peak width lower than 90 nm. Inverse-opal polymeric films with a highly porous and interconnected morphology were obtained using the developed C-PC as a template. Overall, these results showed that reproducible colloidal crystals could be elaborated on a large scale with a simple apparatus in a short period, providing a step forward in the scale-up of the fabrication of photonic colloidal crystal and IO structures as those employed for the elaboration of photonic polymeric sensors.